Development of Kvisoft-Based Flipbook Learning Media on Learning Outcomes in Natural Sciences on the Human Circulatory System - Wilda Jayanti; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2024)
Learning Natural Sciences (IPAS) at SD Negeri 01 Samong faces numerous shortcomings and obstacles, such as a lack of diverse learning resources and suboptimal use of media, which result in low student learning outcomes. This study aims to develop Kvisoft-based flipbook learning media for the Natural Sciences subject, specifically on the human circulatory system for grade V. This type of research is Research and Development (R&D) using the Borg and Gall development model. The population in this study consisted of 57 students, with 12 subjects in a small-scale test in grade VI and 45 subjects in a large-scale test in grade V at SD Negeri 01 Samong. Data collection techniques used include tests (pretest and posttest) and non-test methods such as observation, interviews, questionnaires, and document analysis. The validation results of the Kvisoft-based flipbook media were deemed "very feasible" by media experts with a percentage of 93%, material experts with a percentage of 85% (very feasible category), and language experts with a percentage of 81% (very feasible category). The response from teachers received a 100% rating, and the response from students received a 98% rating, both categorized as "very feasible." Based on the pretest and posttest results, the Kvisoft-based flipbook media was found to be effective in improving student learning outcomes, as evidenced by an increase in the average pretest score from 56.95 to 80.8 in the posttest results. The N-gain test results showed a value of 0.56, indicating a moderate category. From these results, it can be concluded that the Kvisoft-based flipbook media is effective for improving learning outcomes in Natural Sciences on the human circulatory system, and is feasible and practical for use in teaching grade V students at SD Negeri 01 Samong, Pemalang Regency